Enhancing Rabi Brinjal Productivity and Profitability Through Drip Irrigation and Fertigation - Neelima, T. L.; Kumar, K. Avil; Chaitanya, K.; Devi, M. Uma (International Journal of Bio-resource and Stress Management, 2023)
A field experiment was conducted in red sandy loam soils at College Farm, Professor Jayashankar Telangana State Agricultural University (PJTSAU), Telangana, India during the rabi seasons of 2018–19 and 2019–20. The objective of the experiment was to investigate the impact of drip irrigation regimes and fertigation levels on the yield and economic aspects of brinjal during rabi season. The treatments comprised of three levels of irrigation (I1: 0.8 Epan, I2: 1.0 Epan and I3: 1.2 Epan) as main plots and four fertigation levels [F60: 60%; F80: 80%; F100: 100% and F120: 120% of the recommended dose of N and K (150 kg N and 90 kg K2O ha-1)] as subplots, with each treatment replicated thrice. The results indicated that scheduling drip irrigation at 1.0 Epan and fertigation with 100% RDNK resulted in highest fresh fruit yield (41.6 t ha-1), water productivity (0.50 t m-3), net returns (Rs. 1,88,017 ha-1) and benefit: cost (B:C) ratio (2.3) over rest of the treatments. However, this treatment demonstrated comparable yields with that of 120% RDNK applied under the same irrigation regime (1.0 Epan) (41.9 t ha-1), as well as to treatments involving drip irrigation scheduled at 1.2 Epan with fertigation at either 100% (41.8 t ha-1) or 120% (41.9 t ha-1) RDNK. The yield improvement and water saving due to scheduling of drip irrigation at 1.0 Epan in combination with fertigation at 100% RDNK, was to the tune of 28% and 22%, respectively over I0.8F60 (0.8 Epan+60% RDNK) treatment.